Natural Genetic Variation in Yeast Reveals That NEDD4 Is a Conserved Modifier of Mutant Polyglutamine Aggregation. Issue 11 (1st November 2018) - Peters, Theodore W; Nelson, Christopher S; Gerencser, Akos A; Dumas, Kathleen J; Tavshanjian, Brandon; Chang, Kyu Chul; Lithgow, Gordon J; Hughes, Robert E
Abstract: A feature common to late onset proteinopathic disorders is an accumulation of toxic protein conformers and aggregates in affected tissues. In the search for potential drug targets, many studies used high-throughput screens to find genes that modify the cytotoxicity of misfolded proteins. A complement to this approach is to focus on strategies that use protein aggregation as a phenotypic readout to identify pathways that control aggregate formation and maintenance. Here we use natural variation between strains of budding yeast to genetically map loci that influence the aggregation of a polyglutamine-containing protein derived from a mutant form of huntingtin, the causative agent in Huntington disease. Linkage analysis of progeny derived from a cross between wild and laboratory yeast strains revealed two polymorphic loci that modify polyglutamine aggregation. One locus contains the gene RFU1 which modifies ubiquitination states of misfolded proteins targeted by the E3-ubiquitin ligase complex Rsp5 . Activity of the Rsp5 complex, and the mammalian homolog NEDD4, are critical in maintaining protein homeostasis in response to proteomic stress. Our analysis also showed linkage of the aggregation phenotype to a distinct locus containing a gene encoding the Rsp5 -interacting Bul2 protein. Allele-swap experiments validated the impact of both RFU1 and BUL2 on huntingtin aggregation. Furthermore, we found that the nematode Caenorhabditis elegans ' ortholog of Rsp5, wwp-1, also negatively regulates polyglutamine aggregation. Knockdown of the NEDD4 in human cells likewise altered polyglutamine aggregation. Taken together, these results implicate conserved processes involving the ubiquitin regulation network that modify protein aggregation and provide novel therapeutic targets for polyglutamine and other protein folding diseases.